Perspective Study of Spontaneous Resorption of Lumbar Disc Herniation in Female Population of Telangana State, India: Editor's Note: This article has been retracted as of January 2026 as it is out of scope (Indian Journal of Public Health Research & Development, 2023)
Background: Herniation of the disc is the one of the disadvantages human population is facing due to the erect posture. Herniation is the abnormal protrusion of nucleus pulposus from weak site in the annulus fibrosus of the intervertebral disc. It impairs the locomotion of the patients affected with herniation of the disc until the resorption occurs.Method: 30 females aged between 35 to 55 years treated with conservative treatment for low back pain were included in the study. MRI was done to confirm diagnosis and to know the degree of herniation. Routine blood investigations were done to rule out any associated diseases.Results: Out of 30 (12 (40%) were normal, 10 (33.3%) had type-II DM and 8 (26.6%) had HTN. Comparison of spontaneous resorption (in months) 7.5 (±2.4) mean value in large disc, 12.2 (±2.6) in small disc and p value was highly significant (p
Keywords: MRI, Herniation, Spontaneous,Lumbar disc, Telangana